When core beliefs get stuck: Distinct routes to posttraumatic growth and depreciation. (October 2022) - O'Connor, Victoria L.; Langhinrichsen-Rohling, Jennifer; Peterman, Amy H.
Abstract: Posttraumatic growth (PTG) and depreciation are two potential outcomes after a traumatic event. PTG has been defined as the positive psychological changes that can occur when a person derives meaning from the traumatic experience. Depreciation occurs when a person becomes stuck in the trauma, unable to derive meaning. These two outcomes are not well explained under the current model of PTG development, which focuses on how core beliefs are accommodated, or revised, after being violated by traumatic experiences. Accommodation predicts PTG but only partially, or inconsistently predicts depreciation in past research. To address this gap, we add assimilation as an additional cognitive process. Assimilation occurs when traumatic experiences confirm, rather than violate one's world view. We also add perceived trauma severity to the model, as theory requires the event to be impactful in order to affect one's core beliefs. With the addition of these two constructs, we propose a dual-outcome model of cognitive processes leading to the development of PTG and/or depreciation. We hypothesize that core beliefs can be accommodated and/or assimilated following events experienced as traumatic, with accommodation and assimilation differentially predicting PTG and depreciation. This model was tested among young adults betrayed by infidelity, a trauma that is experienced with varying levels of severity. Results support a model in which core belief accommodation was associated with PTG while assimilation was associated with depreciation. Clinical and research implications are discussed.